FRI0283 PRESENTATION AND MANAGEMENT OF GIANT CELL ARTERITIS IN A REAL-WORLD SETTING (ARTEMIS STUDY). (June 2019) - Mahr, Alfred; Paccalin, Marc; Hachulla, Eric; Idier, Isabelle; Devauchelle-Pensec, Valerie
Abstract : Background: We have little real-world data in France on the natural history and management of patients with GCA. Objectives: The objective of this observational study, named ARTEMIS, was to describe the characteristics and management of patients with GCA in real-life settings in France. Methods: This was a cross-sectional, non-interventional, multicentre, single-visit survey, conducted among hospital-based physicians specialized in internal medicine or rheumatology. Investigators enrolled consecutive patients ≥ 50 years old seen for GCA and currently under treatment. Information on medical practices, such as patient characteristics and diagnostic journey, diagnostic methods and specific GCA treatments, were collected on an eCRF. GCA activity was assessed on a 100-mm VAS completed by the patients (PtGA) and physicians (PGA). GCA was considered active for VAS scores ≥10 mm. Newly diagnosed GCA was defined as diagnosis (Dg)-to-visit interval <6 weeks. Onset of symptoms-to-Dg interval was classified as "short" (<1 month), "intermediate" (1–3 months) and "long" (>3 months). Descriptive statistics were used for quantitative and qualitative variables. Results: Over the 3-month inclusion period (August–November 2018), 306 patients were recruited (females: 67.3%, age at Dg ≥70 years: 72.5%); 260 (85.0%) and 46 (15.0%) were followed by internists or rheumatologists, respectively. Overall, 39 (12.7%) had newly diagnosed GCA, 267 (87.3%) had a GCA duration ≥ 6 weeks (mean follow-up 24.0±27.0 months). Original referral of patients to specialized centres was from GPs (55.9%), ophthalmologists (10.1%), neurologists (6.9%), emergency physicians (5.6%), internists (4.2%) and rheumatologists (4.9%). Mean time to Dg was 3.3±6.9 months, with an "intermediate" Dg interval for 57.5% of patients. The most common prior medical histories were hypertension (45.8%), psychiatric disorders (10.1%), dyslipidemia (11.8%), diabetes (9.5%) and osteoporosis (5.9%); during follow-up psychiatric disorders, diabetes and osteoporosis were more often reported: 12.1%, 14.7% and 8.5% of patients respectively. Initial GCA presentations included cranial symptoms (89.5% of patients), constitutional symptoms (73.9%), polymyalgia rheumatica (48.4%), and other extra-cranial manifestations (34.0%). Initial mean ESR and CRP level were 73.0±30.7 mm/hr and 87.3±68.3 mg/l. Temporal artery biopsy, high-resolution temporal artery Doppler ultrasonography, 18 FDG-PET and aortic angio-CT were performed for 84.7%, 31.2%, 26.4% and 29.7% of patients, respectively, and contributed to GCA Dg for 67.1%, 52.7%, 70.3% and 36.8%. At study visit, PtGA was 28.1±26.4 and PGA was 13.1±21.4. Ongoing medications included glucocorticoids (GC) for 273 (89.2%) patients (mean dose: 14.9±16.7 mg/d), methotrexate for 35 (11.4%) and tocilizumab for 44 (14.4%). In total, 122 (39.9%) patients had ≥1 relapse (mean number of relapses: 1.7±1.0) after a mean time to a first relapse of 13.3±12.8 months. Total cumulative oral GC dose was 5179±4987 mg. GCA-related complications occurred in 48 (15.7%) pts with eye disorders in 15 (5.2%). Conclusion: This observational, cross-sectional study of a large number of patients provides insight into current medical practices for GCA in France. Despite extensive use of large-vessel imaging, the proportion of patients diagnosed with non-cranial GCA is small (10%). The substantial proportion of patients with relapsing disease results in high cumulative doses of glucocorticoids. The number of patients with tocilizumab treatment was slightly greater than that with methotrexate treatment. Disclosure of Interests: Alfred Mahr Consultant for: Chugai Pharma France, Speakers bureau: Roche SAS Chugai Pharma France, Marc Paccalin Consultant for: Chugai, Eric Hachulla Consultant for: Received consulting fees or other remuneration from Actelion, GSK, Pfizer, and Bayer, Isabelle Idier Employee of: ChugaiPharma france, Valerie Devauchelle-Pensec Grant/research support from: Roche-Chugai, Speakers bureau: MSD, BMS, UCB, Roche